Occlusal splint associated with auxiliary therapies to control the painful symptomatology of the bruxist patient (Research, Society and Development, 2021)
Objectives: Through a literature review, make a comparison between occlusal splint and auxiliary therapies such as acupuncture, physiotherapy, botulinum toxin and laser therapy for the treatment of bruxism parafunction. Methods: The study used literature from the Scielo, Pubmed, Virtual Health Library and Ebsco databases. Articles in Portuguese and English and with publication date under 11 years were chosen. Literature review: Bruxism is a parafunctional habit resulting from the involuntary contraction of the mastication muscles, especially the masseters and temporalis. The most indicated treatment is the occlusal splint as it is less invasive and has a larger number of studies proving its efficiency. Currently, auxiliary therapies associated with occlusal or isolated splint have shown effective results in reducing the signs and symptoms caused by bruxism. Conclusion: The study concluded that traditional therapy is effective, but when combined with other therapies, it has better results.